2014
DOI: 10.1038/npp.2014.113
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with Novel Brain-Penetrating Selective NOP Receptor Agonist MT-7716 Reduces Alcohol Drinking and Seeking in the Rat

Abstract: Since its discovery, the nociceptin/orphanin FQ (N/OFQ)-NOP receptor system has been extensively investigated as a promising target to treat alcoholism. Encouraging results obtained with the endogenous ligand N/OFQ stimulated research towards the development of novel brain-penetrating NOP receptor agonists with a pharmacological and toxicological profile compatible with clinical development. Here we describe the biochemical and alcohol-related behavioral effects of the novel NOP receptor agonist MT-7716. MT-77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 61 publications
6
45
0
Order By: Relevance
“…This is consistent with a NOP receptor agonist-induced decrease in extracellular dopamine in the NAc (Murphy et al, 1996;Vazquez-DeRose et al, 2013). Nevertheless, the ability of NOP receptor agonists to block self-administration of these drugs appears to be far less robust, if effective at all (Walker et al, 1998;Ciccocioppo et al, 2014;de Guglielmo et al, 2015). One difference in the way in which NOP receptor agonists have been tested in these two "drug abuse" paradigms is that NOP receptor agonists block acquisition of CPP but generally have been tested for their ability to block expression of selfadministration.…”
Section: Future Directions and New Toolssupporting
confidence: 75%
See 1 more Smart Citation
“…This is consistent with a NOP receptor agonist-induced decrease in extracellular dopamine in the NAc (Murphy et al, 1996;Vazquez-DeRose et al, 2013). Nevertheless, the ability of NOP receptor agonists to block self-administration of these drugs appears to be far less robust, if effective at all (Walker et al, 1998;Ciccocioppo et al, 2014;de Guglielmo et al, 2015). One difference in the way in which NOP receptor agonists have been tested in these two "drug abuse" paradigms is that NOP receptor agonists block acquisition of CPP but generally have been tested for their ability to block expression of selfadministration.…”
Section: Future Directions and New Toolssupporting
confidence: 75%
“…In a few recent reports it was shown that N/OFQ acts to suppress glutamate transmission within the central amygdala and that NOP receptor agonists alter GABAergic transmission. It was very recently proposed that activation of N/OFQ-containing cells and receptors in the central amygdala are important for the mediation of anxietylike behavior, responses to stress, and drugs of abuse including alcohol (Cruz et al, 2012;Ciccocioppo et al, 2014;Kallupi et al, 2014). Understanding how N/OFQ and NOP receptors influence neuronal activity within these circuits is a critical next step in our uncovering how NOP receptor activation mediates behavioral affective states.…”
Section: A Electrophysiological Analysis Of Nociceptin Opioid Peptidmentioning
confidence: 99%
“…This hypothesis is additionally supported by data showing that, in msP rats, ethanol intake was enhanced following acute administration of NOP agonists (Economidou et al, 2006a). Conversely, ethanol consumption was progressively decreased following repeated NOP agonist treatment and remained low for several days after treatment discontinuation (Ciccocioppo et al, 2014). This effect may be consistent with the hypothesis that NOP agonists attenuate alcohol drinking through mechanisms involving downregulation or desensitization of NOP receptors (Ciccocioppo et al, 2014).…”
Section: Nop Antagonists Attenuate Ethanol Drinking In Wtsupporting
confidence: 67%
“…Conversely, ethanol consumption was progressively decreased following repeated NOP agonist treatment and remained low for several days after treatment discontinuation (Ciccocioppo et al, 2014). This effect may be consistent with the hypothesis that NOP agonists attenuate alcohol drinking through mechanisms involving downregulation or desensitization of NOP receptors (Ciccocioppo et al, 2014). Indeed, multiple groups have demonstrated rapid and robust NOP receptor desensitization and internalization in vitro in response to either N/OFQ or synthetic NOP agonists (Corbani et al, 2004;Dautzenberg et al, 2001;Spampinato and Baiula, 2006).…”
Section: Nop Antagonists Attenuate Ethanol Drinking In Wtsupporting
confidence: 55%
“…Here, we show that treatment with the NOP agonist, SR-8993, significantly reduced reward-related alcohol intake in nonoperant as well as operant paradigms and that it reduced responding in the progressive-ratio model, indicating reduced motivation to work for alcohol. Most recent studies evaluating the effects of NOP-agonism have focused on its role in negatively reinforced alcohol consumption, in models of enhanced stress sensitivity such as genetically selected msP rats or Wistar rats with a history of alcohol exposure (Ciccocioppo et al 2004;Ciccocioppo et al 2003;Ciccocioppo et al 2014;de Guglielmo et al 2014;Economidou et al 2006). To our knowledge, only one prior study has evaluated the effects of a small-molecule NOP agonist on primary, positive reinforcement by alcohol in nonselected, non-dependent rats.…”
Section: Discussionmentioning
confidence: 99%